Two-Dimensional Ultrasonographic Nomograms of the Fetal Cerebellar Area in aCohort of 150 Normal Singleton Pregnancies: A Prospective Cross-Sectional Study - Firas Abdullah AlBaghdadi (Journal of Biomedicine and Biochemistry, 2025)
Objective: The study aims to set reference ranges for the cerebellar area, across gestation. The fetal cerebellar area is measured in 150 low‑risk pregnancies. The fetal cerebellar area is measured with 2D ultrasonography (2D‑US). Methods: This a prospective cross-sectional study was carried out at specialized gynecology and obstetric center in south of Iraq . We enrolled one hundred fifty women who had a single baby and who had accurate pregnancy dates. Healthy pregnant women were, between 18 and 38 weeks of gestation. We manually tracing ,the outline of cerebellar area in the transverse view of the cerebellum. We performed regression analysis to model the relation between the measured cerebellar area and gestational age (GA). We built reference tables.Results : Women mean age in this study, was 28.7 plus or minus 4.5 years. The mean gestational age at the scan was 27.8 plus or minus 5.1 weeks. We found that the fetal cerebellar area had a linear correlation, with the advancing gestational age. We recorded the correlation coefficient as r = 0.95 and the p value as than 0.001. I derived the regression equation for the area: Cerebellar Area (cm²) = -2.481. 0.257 × GA[weeks]). We created nomograms that show the 95th percentiles, for each gestational week from 18 to 38 weeks. We did not find a correlation between the area and the maternal Body Mass Index (BMI). The correlation was (r = 0.08 p = 0.32The study provides 2D‑US nomograms, for the cerebellar area from a cohort of 150 patients. The 2D‑US nomograms are a simple tool. The 2D‑US nomograms serve as a tool in prenatal screening, for posterior fossa anomalies.